Spatial analysis of traffic accidents on the Baghdad-Diyala road (Old Road) for the period from 2019-2023 (Journal of the College of Basic Education, 2025)
The old Baghdad-Diyala road is one of the important main roads in Iraq due to its great importance as it connect Baghdad with Diyala from the east of Baghdad, and it's great importance has led to the creation of a density of transport traffic on the road, especially transport vehicles (trucks and tankers of oil products). This is due to the presence of the Khan Bani Saad silo and the Rusafa oil depot on the road to the study. In addition to that, there are some fuel filling stations and many schools, while the road consists of one side, back and forth, which results in accidents occurring in deadly traffic. Due to the importance of the road, it was studied by analyzing the traffic accidents that occurred on this Baghdad-Diyala road (the old road) for the period from (2019-2024) in terms of the number of accidents, deaths, and injuries therein. Then, the accidents, deaths, and injuries were distributed according to the road sections divided by the researcher, It was found, through collecting data from the General Directorate of Traffic in Baghdad and Al-Zawraa area, that the total number of traffic accidents occurring on the road in the study area amounted to (293) traffic accidents, (100) deaths, and (700) injuries. The highest number of accidents was recorded in a year(2022) with (72) traffic accidents, (25) deaths, and (123) injuries. The least recorded year for traffic accidents was the year (2020), with (39) traffic accidents, (11) deaths, and (104) injuries.